POST - SLAUGHTER FACTORS THAT CONTRIBUTE TO MEAT TENDERNESS - Simeoni, Caroline Posser; Fruet, Ana Paula Burin; Menezes, Maria Fernanda Cáceres; Kirinus, Jackeline Karsten; Teixeira, César; Ritt, Luciano Antonio (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
The chain of meat production features prominent and increasing consumer requirements, research related to product quality are being widely developed position. Among the characteristics of meat quality, tenderness is considered the most influential characteristic for consumer satisfaction. In order to evaluate the main factors that influence respondents in meat tenderness, an analysis was performed through a literature review of the procedures that contribute to the softness in post mortem, such as enzyme maturation, pH, cooling rate, stimulation electric, how to hang and tenderization carcasses. These factors are related to postmortem examinations are considered the most important in the final product of tenderness.